Comparative exergoeconomic assessment of coal-fired power plants – Binary Rankine cycle versus conventional steam cycle. (1st January 2018) - Hofmann, Mathias; Tsatsaronis, George
Abstract: This article describes an analysis of both a binary and a conventional Rankine cycle for a coal-fired power plant. The major question is whether it is possible to compensate the expected higher capital investment associated with additional components by a lower fuel consumption during the operation. By implementing an exergy analysis, the concept of a binary Rankine cycle with potassium and water as working fluids is compared to a conventional coal-fired power plant. Furthermore, an exergoeconomic analysis is carried out in order to understand the formation and flow of costs in the systems. With the help of sensitivity analyses, we show the impact of uncertain economic parameters, such as fuel cost, capacity factor, or capital investment on the levelized cost of electricity. The comparative exergoeconomic analysis shows that the concept of a binary Rankine cycle is suitable for fuel and emission reduction and economically viable. Under certain conditions, such as a sufficient number of annual equivalent full-load hours, an advantage arises over a conventional coal-fired power plant. Highlights: A binary Rankine cycle enables emission reductions and fuel savings. The concept is compared in detail with a conventional coal-fired power plant. The assessment evaluates the advantages of a binary Rankine cycle. Graphical representations show the sensitivity of uncertain parameters. Exergoeconomic evaluations identify potential for improvement.